A cage-shaped cobalt iron sulfide carbon nanofiber composite material and its preparation method and application
Cobalt-iron Prussian blue is combined with carbon nanofibers through electrospinning technology to form a cage-shaped cobalt-iron chalcogenide carbon nanofiber composite material, solving the volume change and insufficient conductivity of PBAs-derived metal chalcogenides during charging and discharging. The problem is that the long cycle stability and good rate performance of the negative electrode material of sodium ion battery are achieved.
Patent Information
- Application Number
- CN202310469850.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-27
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-04-27
AI Technical Summary
Metal chalcogenides derived from PBAs are prone to agglomeration and structural collapse during the charge and discharge cycle, resulting in rapid capacity decay, short cycle life and slow ion transmission kinetics.
Cobalt-iron Prussian blue is composited with carbon nanofibers through electrospinning technology to form a cage-shaped cobalt-iron chalcogenide carbon nanofiber composite material, alleviating volume changes and improving conductivity.
As the negative electrode material of sodium ion battery, this composite material has long cycle stability and good rate performance, which significantly improves the electrochemical performance of the electrode material.
Smart Images

Figure CN116497595B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of sodium ion battery electrode materials, and in particular to a cage-shaped cobalt iron sulfide carbon nanofiber composite material and a preparation method thereof and application thereof as a sodium ion battery negative electrode material. Background Art
[0002] In recent years, with the development of society, energy and environmental issues have become two major challenges facing human society today. Lithium-ion batteries have become the preferred choice of new power sources due to their advantages such as high operating voltage, long cycle life and high energy density. However, due to the scarcity of lithium resources, people are in urgent need of finding suitable alternatives. Sodium-ion batteries are considered to be an excellent alternative to lithium-ion batteries because of their similar working principles, abundant raw materials and low price.
[0003] Prussian blue analogs (PBAs) are a typical coordination framework material, which can be expressed as x M1[M2(CN)6] y ·ZH2O, where M1 / M2 are transition metals connected by cyano groups, and A is a cation embedded in the gap of the PBA framework. Due to its low cost, easy preparation, inherent open framework and designable components, it is considered to be a sodium-ion battery electrode material with great development potential. Metal sulfide derived from PBAs can better retain the inherent framework structure of Prussian blue, and the metal-sulfur bond or metal-selenium bond in metal sulfide is weaker than the corresponding metal-oxygen bond in metal oxide, which is kinetically favorable for conversion reaction with sodium ions. However, during the charge and discharge cycle, metal sulfide derived from PBAs is still prone to agglomeration and structural collapse, resulting in rapid capacity decay, short cycle life and slow ion transport kinetics. These problems greatly limit the application of PBAs-derived metal sulfide materials. Summary of the invention
[0004] The main purpose of the present invention is to provide a preparation method and application of a cage-like cobalt iron sulfide carbon nanofiber composite material in view of the above problems. The preparation method involved in the present invention is simple, a hollow cage structure can be obtained without etching, and it can be prepared in large quantities. The volume change of PBAs-derived sulfide during the charge and discharge process is alleviated and the conductivity is improved by compounding with carbon materials through electrospinning technology. The composite material has excellent long-cycle stability and rate performance as a negative electrode material for sodium ion batteries.
[0005] To achieve the above solution, the technical solution adopted by the present invention is:
[0006] The present invention provides a method for preparing a cage-shaped cobalt iron sulfide carbon nanofiber composite material, comprising the following steps:
[0007] (1) dissolving an appropriate amount of potassium ferrocyanide in an appropriate amount of deionized water to form a yellow transparent solution A;
[0008] (2) dissolving cobalt salt and trisodium citrate dihydrate in deionized water to obtain a pink transparent solution B;
[0009] (3) Solution A and Solution B are mixed, allowed to stand for a period of time at a certain temperature, centrifuged, washed, and dried to obtain a purple solid powder, i.e., caged cobalt iron Prussian blue;
[0010] (4) dissolving the caged cobalt iron Prussian blue and the high molecular polymer obtained in step (3) in N,N-dimethylformamide to form a spinning precursor solution;
[0011] (5) electrospinning the spinning precursor solution to obtain a purple film α;
[0012] (6) Pre-oxidizing the purple film α at low temperature in air and pyrolyzing it at high temperature in an inert atmosphere to obtain a black film β;
[0013] (7) The black film β is heat-treated with a sulfur source or a selenium source under the protection of an inert gas to obtain a caged cobalt disulfide / iron disulfide carbon nanofiber or a caged cobalt diselenide / iron diselenide carbon nanofiber composite material.
[0014] Preferably, in the steps (1) to (2), the molar ratio of potassium ferrocyanide to cobalt salt to trisodium citrate dihydrate is (0.5-4):(1-6):(1-10); and the cobalt salt is any one of cobalt acetate tetrahydrate, cobalt chloride hexahydrate or cobalt nitrate hexahydrate.
[0015] Preferably, in step (3), the standing time is 20 to 72 hours and the standing temperature is 30 to 80°C.
[0016] Preferably, in step (4), the mass ratio of the caged cobalt iron Prussian blue to the high molecular polymer is 1:(0.5-5); the mass ratio of the high molecular polymer to N,N-dimethylformamide is 1:(7-15);
[0017] The high molecular polymer is any one of polyacrylonitrile, polyvinyl pyrrolidone or polyvinyl alcohol.
[0018] Preferably, in step (5), the electrospinning voltage is 10-20 kV, the receiving distance is 10-20 cm, and the pushing speed is 0.4-1.2 mL h -1 .
[0019] Preferably, in step (6), the pre-oxidation temperature is 200-280° C., and the holding time is 1-3 h;
[0020] The pyrolysis temperature is 500-900℃, and the heating rate is 2-5℃min -1 , the insulation time is 1 to 4 hours, and the inert atmosphere is nitrogen or argon.
[0021] Preferably, in step (7), the heat treatment temperature is 400-600°C, and the heating rate is 2-5°C min -1 , the holding time is 1 to 4 hours, the inert atmosphere is nitrogen or argon
[0022] The sulfur source is any one of sulfur powder, thiourea or thioacetamide, and the selenium source is selenium powder;
[0023] The mass ratio of the black film β to the sulfur source or the selenium source is 1:(2-6).
[0024] In the above steps, the main reactions are as follows: First, the metal cobalt ions react with ferrocyanide to form a cobalt iron Prussian blue precursor, in which trisodium citrate dihydrate plays a role in complex stabilization. At a certain temperature, electron transfer occurs in the precursor molecule and induces the structure to transform into a cage-like nanoframe. The film obtained by electrospinning technology is pre-oxidized in the air to stabilize the fiber structure, and then high-temperature carbonization is performed to decompose the polymer into nitrogen-doped carbon, and the cobalt iron Prussian blue is converted into a cobalt iron alloy under carbon reduction; finally, gas phase sulfurization or selenization treatment is performed, and the sulfur source or selenium source sublimates at high temperature to become sulfur or selenium vapor, which reacts with the cobalt iron alloy to form cobalt disulfide / iron disulfide or cobalt diselenide / iron diselenide, and the excess sulfur or selenium is removed in the form of gas.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The present invention prepares a uniform cage-shaped cobalt-iron Prussian blue precursor by a coprecipitation method at a certain temperature, and the particle size is about 200 nm. The preparation method is simple, the reaction conditions are simple, the morphology and size are controllable, and a hollow cage structure can be formed without etching, which can alleviate the volume change of the electrode material during the charge and discharge process.
[0027] (2) The cobalt-iron Prussian blue-derived cobalt-iron sulfide-carbon nanofiber composite material prepared by the present invention retains the unique framework structure of the precursor well, which is beneficial to improving the electrochemical performance of the electrode material.
[0028] (3) The present invention encapsulates Prussian blue-derived cobalt iron sulfide into carbon nanofibers through electrospinning technology, thereby inhibiting the self-agglomeration of metal sulfide. Due to the protective effect of the nanofiber component and the enhanced adhesion between the nanofiber and the active component, the volume effect of the electrode active material can be inhibited and the cycle stability of the electrode material can be improved. The two-component transition metal sulfide forms a heterojunction, which can adjust the electronic structure of the single-component material, and the interface and space confinement effects can synergistically enhance the electrochemical performance of the negative electrode material.
[0029] (4) The present invention combines multiple means to alleviate the volume effect of sulfide during the charge and discharge process and improve its conductivity. The composite material has a long cycle life and good electrochemical performance as a negative electrode material for sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the X-ray diffraction pattern of the cage-like cobalt disulfide / iron disulfide carbon nanofibers prepared in Example 1.
[0031] Figure 2 This is a scanning electron microscope image of the caged cobalt-iron Prussian blue prepared in Example 1.
[0032] Figure 3 This is a scanning electron microscope image of the cage-like cobalt disulfide / iron disulfide carbon nanofibers prepared in Example 2.
[0033] Figure 4 This is a rate performance diagram of the caged cobalt disulfide / iron disulfide carbon nanofibers prepared in Example 1.
[0034] Figure 5 This is a graph showing the cycle performance of the caged cobalt disulfide / iron disulfide carbon nanofibers prepared in Example 2.
[0035] Figure 6 This is the X-ray diffraction pattern of the caged cobalt diselenide / iron diselenide carbon nanofibers prepared in Example 4.
[0036] Figure 7 This is a rate performance diagram of the caged cobalt disulfide / iron disulfide carbon nanofibers prepared in Example 5.
[0037] Figure 8 This is a graph showing the cycle performance of the caged cobalt disulfide / iron disulfide carbon nanofibers prepared in Example 6. DETAILED DESCRIPTION
[0038] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited thereto.
[0039] Example 1
[0040] 1) Weigh 0.75 g of cobalt acetate tetrahydrate and 0.74 g of trisodium citrate dihydrate and dissolve them in 100 mL of water (solution A), and dissolve 0.65 g of potassium ferrocyanide in 100 mL of water (solution B). Mix solution A and solution B evenly, let stand at 60° C. for 32 h, centrifuge, wash, and dry to obtain caged cobalt iron Prussian blue (Co-Fe PBA).
[0041] 2) Weigh 0.45 g of Co-Fe PBA and add 12 g of N,N-dimethylformamide (DMF). After ultrasonic dispersion, add 0.9 g of polyacrylonitrile (PAN, Aladdin, Mw: 149000-151000) and stir to obtain a spinning solution.
[0042] 3) The obtained spinning solution precursor was poured into a 5 mL syringe, the spinning voltage was set to 14 kV, the receiving distance was 15 cm, and the pushing speed was 0.6 mL h -1 , and a cage-like Co-Fe PBA / PAN composite nanofiber film was obtained by spinning.
[0043] 4) The film obtained in (3) was pre-oxidized at 260°C for 2 h in air atmosphere and then heated at 2°C min in nitrogen atmosphere. -1 The temperature was raised to 600°C at a heating rate and kept at this temperature for 2 h to obtain a black film β.
[0044] 5) Take 0.2g sulfur powder and 0.07g black film β and place them at the two ends of the quartz boat respectively. -1 The temperature was raised to 500°C at a heating rate and kept at this temperature for 1.5 h to obtain a cage-like cobalt disulfide / iron disulfide carbon nanofiber composite material (CoS2 / FeS2@CNFs).
[0045] Example 2
[0046] 1) Weigh 0.88 g of cobalt nitrate hexahydrate and 1.76 g of trisodium citrate dihydrate and dissolve them in 100 mL of water (solution A), and dissolve 0.66 g of potassium ferrocyanide in 100 mL of water (solution B). Mix solution A and solution B evenly, let stand at 80° C. for 20 h, centrifuge, wash, and dry to obtain a caged Co-Fe PBA.
[0047] 2) Weigh 0.45 g of Co-Fe PBA and add 10 g of DMF. After ultrasonic dispersion, add 0.9 g of PAN (Aladdin, Mw: 149000-151000) and stir vigorously to obtain a spinning solution.
[0048] 3) The obtained spinning solution was poured into a 5 mL syringe, the spinning voltage was set to 12 kV, the receiving distance was 20 cm, and the pushing speed was 1.0 mL h -1, and a cage-like Co-Fe PBA / PAN composite nanofiber film was obtained by spinning.
[0049] 4) The film obtained in (3) was pre-oxidized at 220°C for 3 h in air atmosphere and then heated at 5°C min-1 under nitrogen protection. -1 The temperature was raised to 800°C at a heating rate and kept at that temperature for 1 h to obtain a black film β.
[0050] 5) Take 0.5g thiourea and 0.15g black film β and place them at the two ends of the quartz boat respectively. -1 The temperature was raised to 450 °C at a heating rate and kept for 2 h to obtain cage-like CoS2 / FeS2@CNFs.
[0051] Example 3
[0052] 1) Weigh 0.57 g of cobalt chloride hexahydrate and 0.6 g of trisodium citrate dihydrate and dissolve them in 80 mL of water (solution A), and dissolve 0.53 g of potassium ferrocyanide in 80 mL of water (solution B). Mix solution A and solution B evenly, let stand at 50° C. for 36 h, centrifuge, wash, and dry to obtain a caged Co-Fe PBA.
[0053] 2) Weigh 0.3 g of Co-Fe PBA and add 8 g of DMF. After ultrasonic dispersion, add 0.9 g of polyvinyl pyrrolidone (PVP, Aladdin, Mw: 1300000) and stir vigorously to obtain a spinning solution.
[0054] 3) The obtained spinning solution was poured into a 5 mL syringe, the spinning voltage was set to 12 kV, the receiving distance was 18 cm, and the pushing speed was 0.8 mL h -1 , and the Co-Fe PBA / PVP composite nanofiber film was obtained by spinning.
[0055] 4) The film obtained in (3) was pre-oxidized at 280°C for 1 h in air atmosphere and then heated at 2°C min-1 under nitrogen protection. -1 The temperature was raised to 700°C at a heating rate and kept at that temperature for 2 h to obtain a black film β.
[0056] 5) Take 0.5g of thioacetamide and 0.25g of black film β and place them at the two ends of the quartz boat respectively. -1 The heating rate was raised to 600℃ and kept at this temperature for 1h to obtain cage-like CoS2 / FeS2@CNFs.
[0057] Example 4
[0058] 1) Weigh 0.9 g of cobalt acetate tetrahydrate and 1.18 g of trisodium citrate dihydrate and dissolve them in 100 mL of water (solution A), and dissolve 0.87 g of potassium ferrocyanide in 100 mL of water (solution B). Mix solution A and solution B evenly, let stand at 70° C. for 24 h, centrifuge, wash, and dry to obtain a caged Co-Fe PBA.
[0059] 2) Weigh 0.336 g of Co-Fe PBA and add 9 g of DMF. After ultrasonic dispersion, add 0.9 g of PAN (Aladdin, Mw: 149000-151000) and stir vigorously to obtain a spinning solution.
[0060] 3) The obtained spinning solution was poured into a 5 mL syringe, the spinning voltage was set to 18 kV, the receiving distance was 20 cm, and the pushing speed was 1.2 mL h -1 , and the Co-Fe PBA / PAN composite nanofiber film was obtained by spinning.
[0061] 4) The film obtained in (3) was pre-oxidized at 280°C for 1 h in air atmosphere and then heated at 5°C min-1 under argon protection. -1 The temperature was raised to 700°C at a heating rate and kept at that temperature for 1 h to obtain a black film β.
[0062] 5) Take 0.3g of selenium powder and 0.15g of black film β and place them at the two ends of the quartz boat respectively. -1 The heating rate was increased to 350℃ and kept for 2h to obtain cage-like CoSe2 / FeSe2@CNFs.
[0063] Example 5
[0064] 1) Weigh 0.88 g of cobalt nitrate hexahydrate and 1.76 g of trisodium citrate dihydrate and dissolve them in 100 mL of water (solution A), and dissolve 0.66 g of potassium ferrocyanide in 100 mL of water (solution B). Mix solution A and solution B evenly, let stand at 70° C. for 28 h, centrifuge, wash, and dry to obtain a caged Co-Fe PBA.
[0065] 2) Weigh 0.9 g of Co-Fe PBA and add 12 g of DMF. After ultrasonic dispersion, add 0.9 g of PVP (Aladdin, Mw: 1,300,000) and stir vigorously to obtain a spinning solution.
[0066] 3) The obtained spinning solution was poured into a 5 mL syringe, the spinning voltage was set to 10 kV, the receiving distance was 12 cm, and the pushing speed was 0.4 mL h -1 , and the Co-Fe PBA / PVP composite nanofiber film was obtained by spinning.
[0067] 4) The film obtained in (3) was pre-oxidized at 200°C for 3 h in air atmosphere and then heated at 2°C min-1 under nitrogen atmosphere. -1 The temperature was raised to 900°C at a heating rate and kept at this temperature for 3 h to obtain a black film β.
[0068] 5) Take 0.3g sulfur powder and 0.08g black film β and place them at the two ends of the quartz boat respectively. -1 The heating rate was increased to 500℃ and kept for 3h to obtain cage-like CoS2 / FeS2@CNFs.
[0069] Example 6
[0070] 1) Weigh 1 g of cobalt acetate tetrahydrate and 1.8 g of trisodium citrate dihydrate and dissolve them in 100 mL of water (solution A), and dissolve 0.66 g of potassium ferrocyanide in 100 mL of water (solution B). Mix solution A and solution B evenly, let stand at 65° C. for 24 h, centrifuge, wash, and dry to obtain a caged Co-Fe PBA.
[0071] 2) Weigh 0.9 g of Co-Fe PBA and add 12 g of DMF. After ultrasonic separation, add 0.9 g of polyvinyl alcohol (PVA, (Aladdin, 1788 type)) and stir vigorously to obtain spinning.
[0072] 3) The obtained spinning solution was poured into a 5 mL syringe, the spinning voltage was set to 15 kV, the receiving distance was 18 cm, and the pushing speed was 0.9 mL h -1 , and the Co-Fe PBA / PVA composite nanofiber film was obtained by spinning.
[0073] 4) The film obtained in (3) was pre-oxidized at 280°C for 1 h in air atmosphere and then heated at 5°C min-1 under argon protection. -1 The temperature was raised to 500°C at a heating rate and kept at this temperature for 4 h to obtain a black film β.
[0074] 5) Take 0.6g thiourea and 0.12g black film β and place them at the two ends of the quartz boat respectively. -1 The temperature was raised to 400℃ at a heating rate and kept for 4h to obtain cage-like CoS2 / FeS2@CNFs.
[0075] Performance Testing
[0076] The caged cobalt disulfide / iron disulfide carbon nanofibers or caged cobalt diselenide / iron diselenide carbon nanofibers obtained in Examples 1 to 6 were ground and stirred with a conductive agent Super P and a binder polyvinylidene fluoride in a certain mass ratio until they were evenly mixed, coated on a copper foil, and then punched into discs with a diameter of 12 mm as the negative electrode, metallic sodium as the counter electrode, 1 M sodium hexafluorophosphate (NaPF6) dissolved in dimethyl ether as the electrolyte, and glass fiber as the diaphragm. They were assembled into CR2025 button batteries in a glove box filled with argon atmosphere and with a water oxygen value of less than 0.01 ppm. After being left for 24 hours, constant current charge and discharge tests were performed using a Xinwei tester in the range of 0.01 to 3 V.
[0077] Figure 1 : is the XRD spectrum of Example 1, which shows that the phases are cobalt disulfide with a pyrite structure (JCPDS No. 41-1471) and iron disulfide with a pyrite structure (JCPDS No. 42-1340). Figure 2 The XRD spectrum of Example 4 shows that the phases are cobalt diselenide (JCPDS No. 53-0449) and iron diselenide (JCPDS No. 79-1892). Figure 3 This is a SEM image of the cage-like Co-Fe PBA prepared in Example 1. It can be seen that it has a hollow cubic structure, and the average diameter of the cubic block is about 200 nm. Figure 4 This is the SEM image of Example 2, which shows that the carbon nanofibers with rough surfaces are interwoven into a network structure, cage-like cobalt disulfide / iron disulfide is encapsulated inside the fibers, and the average fiber diameter is about 400 nm.
[0078] Figure 5 The rate performance test results of Example 1 are shown in the figure. -1 , 0.5Ag -1 , 1Ag -1 , 2A g -1 , 5A g -1 and restore 0.2A g -1 The specific capacity at the current density of 471.2 mAh g -1 , 444.2mAh g -1 、426.1mAh g -1 、397.8mAh g -1 、329.2mAh g -1 and 526.2mAh g -1 , showing excellent rate performance. Figure 6 The cycle performance diagram shows that the sodium ion battery has a -1 The capacity after 150 cycles at a current density of 483.1 mAh g-1 , the capacity retention rate is close to 100%, showing excellent cycle stability.
[0079] The cage-shaped cobalt iron sulfide carbon nanofiber composite materials in Examples 1-6 are used as negative electrode materials for sodium ion batteries and assembled into sodium ion batteries with discharge specific capacities at different current densities as shown in Table 1:
[0080]
[0081] As can be seen from the table, changing the feed ratio of Prussian blue and high molecular polymer or the pyrolysis temperature will have a certain effect on the performance of the electrode material. This may be because the content of high molecular polymer as a carbon source will have a certain limiting effect on the improvement of specific capacity, and the pyrolysis temperature will affect the degree of graphitization and thus affect the volume change of the electrode material during the charge and discharge process. In the last step of heat treatment, changing the sulfur source to a selenium source significantly reduces the capacity. This is because although the sodium storage mechanism of cobalt iron sulfide and cobalt iron selenide is similar, the relative atomic mass of sulfur is smaller than that of selenium, so the theoretical sodium storage capacity of cobalt iron sulfide is higher than that of cobalt iron selenide.
[0082] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; unless otherwise specified, they are all conventional methods in the art.
[0083] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a cage-shaped cobalt iron sulfide carbon nanofiber composite material for a negative electrode of a sodium ion battery, characterized in that The following steps are involved: (1) Dissolve potassium ferrocyanide in deionized water to form a yellow transparent solution A; (2) Dissolve cobalt salt and trisodium citrate dihydrate in deionized water to obtain a pink transparent solution B; (3) Mix solution A and solution B, let stand at 30-80°C for 20-72 hours, centrifuge, wash, and dry to obtain a purple solid powder, i.e., caged cobalt iron Prussian blue; (4) dissolving the caged cobalt iron Prussian blue and high molecular polymer obtained in step (3) in N , N - forming a spinning precursor solution in dimethylformamide; The mass ratio of caged cobalt iron Prussian blue to high molecular polymer is 1:(0.5~5); Polymers and N , N -The mass ratio of dimethylformamide is 1:(7~15); (5) electrospinning the spinning precursor solution to obtain a purple film α; (6) The purple film α is pre-oxidized in air and then pyrolyzed under an inert atmosphere to obtain a black film β; The pre-oxidation temperature is 200-280°C and the holding time is 1-3h; The pyrolysis temperature is 500-900°C, and the heating rate is 2-5°C min -1 , the holding time is 1~4h, and the inert atmosphere is nitrogen or argon; (7) heat-treating the black film β with a sulfur source or a selenium source under inert atmosphere protection to obtain a caged cobalt iron sulfide carbon nanofiber composite material, that is, a caged cobalt disulfide / iron disulfide carbon nanofiber composite material or a caged cobalt diselenide / iron diselenide carbon nanofiber composite material, wherein the caged cobalt disulfide / iron disulfide or cobalt diselenide / iron diselenide is encapsulated inside the carbon nanofiber, the fibers are interwoven into a network structure, and the surface is rough; The sulfur source is sulfur powder, thiourea or thioacetamide, and the selenium source is selenium powder; The heat treatment temperature is 400-600°C, and the heating rate is 2-5°C min -1 , the insulation time is 1~4h, and the inert atmosphere is nitrogen or argon.
2. The preparation method according to claim 1, characterized in that : In steps (1) to (2), the molar ratio of potassium ferrocyanide, cobalt salt and trisodium citrate dihydrate is (0.5-4): (1-6): (1-10); The cobalt salt is any one of cobalt acetate tetrahydrate, cobalt chloride hexahydrate or cobalt nitrate hexahydrate.
3. The preparation method according to claim 1, characterized in that: In step (4), the high molecular polymer is polyacrylonitrile, polyvinyl pyrrolidone or polyvinyl alcohol.
4. The preparation method according to claim 1, characterized in that: In step (5), the electrospinning conditions are: spinning voltage is 10-20 kV, receiving distance is 10-20 cm, and pushing speed is 0.4-1.2 mL h -1 .
5. The preparation method according to claim 1, characterized in that: In step (7), the mass ratio of the black film β to the sulfur source or selenium source is 1:(2-6).
6. The cage-like cobalt iron sulfide carbon nanofiber composite material obtained by the preparation method according to any one of claims 1 to 5.
7. Use of the cage-like cobalt iron sulfide carbon nanofiber composite material according to claim 6 as a negative electrode material for sodium ion batteries.
Citation Information
Patent Citations
Preparation method of prussian blue analogue nano-material and use of prussian blue analogue in sodium-ion battery
CN105990567A
Application of high-performance supercapacitor electrode material Co-Fe-type Prussian blue nanocube
CN108083293A
Preparation method and application of waxberry-shaped iron-doped cobalt-based chalcogenide nitrogen-doped carbon porous composite material
CN115425209A
Cited By
Preparation method and application of multi-channel carbon nanofiber composite material with high load of ferrocobalt sulfide
CN120033190A